Changing Medium: The Contemporary Reception of Joseph Conrad’s Heart of Darkness in Two Graphic Novels - Nathalie Martinière (Sillages Critiques)
A number of contemporary authors/artists have chosen not to “write back” vehemently to what they find problematic in Joseph Conrad’s Heart of Darkness, but to resort to a different medium and “rewrite” or adapt the novella as a graphic novel, as if the power of images could clarify the text for 21st-century readers. Changing medium and associating text and image enables them to underline the historical context, tackle elements in the stories that would otherwise remain largely unnoticed, and therefore problematize its ambiguities, as is the case in Anyango and Mairowitz’s Heart of Darkness (2010) and Au cœur des ténèbres. Librement adapté du roman de Joseph Conrad (Miquel and Godart, 2014). Changing medium allowed them to revisit both the colonial past and the meaning of a novella like Heart of Darkness since both graphic novels perform an implicit criticism of the source text and serve to reexamine its controversial aspects in the 21st century. Interestingly, in one case it implies the spectral presence of the novelist, Joseph Conrad as if, in a postcolonial context, a text could not be separated from the figure of its author.